2002
DOI: 10.1093/annhyg/mef007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sampling Time on the Culturability of Airborne Fungi and Bacteria Sampled by Filtration

Abstract: Air sampling of bioaerosols by filtration may be preferable for many epidemiological studies because the methods can be used to collect personal samples for a full work-shift. There is some concern, however, that the viability of fungal spores and bacterial cells might be compromised by sampling for as long as a full shift. This study was designed to determine the effect of sampling up to 6 h on the viability (measured by culture) of airborne fungi and bacteria at composting facilities. Six side-by-side sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The results obtained in these experiments have shown that five- or tenfold increase in volume of the air samples collected (due to increase in sampling time at the same velocity of air flow) did not result in an increase of the mean number of the culturable microorganisms. Similar results have already been reported by Durand et al (2002) who used filtration method of air sampling at the composting facilities. The authors have demonstrated that increase in sampling time up to 6 h at a stable air flow of 2 l/min did not affect the mean number of culturable bacteria in 1 m 3 of the air that contained bacteria at the relatively constant concentration in a period of time when the air samples were collected.…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained in these experiments have shown that five- or tenfold increase in volume of the air samples collected (due to increase in sampling time at the same velocity of air flow) did not result in an increase of the mean number of the culturable microorganisms. Similar results have already been reported by Durand et al (2002) who used filtration method of air sampling at the composting facilities. The authors have demonstrated that increase in sampling time up to 6 h at a stable air flow of 2 l/min did not affect the mean number of culturable bacteria in 1 m 3 of the air that contained bacteria at the relatively constant concentration in a period of time when the air samples were collected.…”
Section: Discussionsupporting
confidence: 90%
“…Because the sampling principle of filters is filtration, once bioaerosols are trapped, they must undergo desiccation before the sampling ends, which possibly causes the loss of viability [ 50 , 51 ]. Durand et al [ 52 ] investigated the effect of sampling time on the viability of airborne fungi and bacteria. They used the 37-mm Filter Cassette sampler (2 L/min), along with the 0.8-μm PC filters for sampling at six composting facilities with high bioaerosol exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This requires a trade-off between sampling periods short enough to avoid desiccation or damage to samples against long enough to sample sufficient biomass to give meaningful data. To this end, Durand et al (2002) investigated the effect of sample time on the culturability of airborne fungi and bacteria sampled by filtration, reporting no loss in viability. There are already studies of this type, and it is anticipated that a variety of approaches will enhance the quality of the data.…”
Section: Methodsmentioning
confidence: 99%